1988
DOI: 10.1128/jcm.26.2.250-256.1988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medium and inoculum variations on screening for high-level aminoglycoside resistance in Enterococcus faecalis

Abstract: Enterococcus faecalis isolates that are refractory to aminoglycoside-penicillin synergy can be detected by their ability to grow in the presence of high concentrations of aminoglycoside (2,000 ,g/ml). In past studies investigators have used a variety of media and inoculum sizes to perform high-level aminoglycoside resistance screens, but little is known about how these variations affect test accuracy. We screened 63 E. faecalis strains on different media by using various inoculum sizes and correlated the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

1989
1989
2002
2002

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 22 publications
2
20
1
Order By: Relevance
“…Results of this investigation and those of previous studies have shown that false aminoglycoside susceptibility, not false resistance, is the problem most frequently encountered with available screening methods (2,4,12,15,17,18,21). In this investigation prolonging of the incubation time to 48 h substantially increased the percentage of resistant strains detected.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Results of this investigation and those of previous studies have shown that false aminoglycoside susceptibility, not false resistance, is the problem most frequently encountered with available screening methods (2,4,12,15,17,18,21). In this investigation prolonging of the incubation time to 48 h substantially increased the percentage of resistant strains detected.…”
Section: Discussionmentioning
confidence: 49%
“…These findings are consistent with those of several previous studies which showed that false susceptibility occurs more frequently with streptomycin testing (2,4,14,15,(17)(18)(19). In an earlier study, false streptomycin susceptibility occurred most frequently with the use of a low inoculum (102 CFU/ml) on either Mueller-Hinton or Trypticase soy agar (12). However, it is not yet known whether discrepancies in the results for streptomycin are related to media, inoculum size, or strain characteristics.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies have been conducted to validate the accuracy of antimicrobial susceptibility testing of VRE [4,5]. The composition of plating/broth medium and the growth conditions of enterococcal isolates may in£uence the antibiotic susceptibility pro¢les and the minimum inhibitory concentration (MIC) values [6,7]. The effect of plating medium, however, was not correlated with the presence of vancomycin resistance genes in these studies.…”
Section: Introductionmentioning
confidence: 95%
“…For those strains that did not grow, antibiotic MICs were <1,000 pLg of gentamicin per ml or <2,000 Vag of streptomycin per ml (135, 152; unpublished observations). Sahm and Torres evaluated dextrose phosphate agar, brain heart infusion agar, Mueller-Hinton agar with 5% sheep blood, and Trypticase soy agar with 5% sheep blood with different inocula of E. faecalis to screen for HLR (181). Excellent results were obtained with inocula of 104 and 106 CFU per spot with both gentamicin and streptomycin regardless of the medium used.…”
Section: Screening Tests For High-level Aminoglycoside Resistancementioning
confidence: 99%